Permanent cutaneous vesicostomy: a pragmatic approach to safely manage lower urinary tract dysfunction in pediatric patients with chronic and life-limiting conditions and neuropathic bladders - Vallasciani, Santiago; Al Saeedi, Ahmed; Khalil, Ibrahim A.; Mohamed, Reem Babiker; Muneer, Eshan; Abdelmaguid, Nadra; Pippi Salle, Joao Luiz (Frontiers in Pediatrics, 2024)
Lower urinary tract dysfunction (LUTD) in Cerebral Palsy (CP) and other neuromuscular diseases can present with chronic retention that leads to hydronephrosis, recurrent Urinary Tract Infections (UTI), and stone formation . Whenever the conservative treatment of LUTD fails for any reason it is considered as complicated LUTD , in which a surgical approach is warranted . Cutaneous Vesicostomy (CV) is a simple, well-tolerated, and potentially reversible that protects the upper tracts. We describe our experience with using CV for this complex population.Children with CP and other neuromuscular diseases admitted to pediatric long-term care units for palliative care. They present multi-system involvement, polypharmacy, and Gross Motor Function Classification System (GMFCS) levels of 4 or 5. We retrospectively studied this population's indications and results of CV between 2015 and 2019.Results: 18 out of the 52 admitted patients presented LUTD with UTI (18 -100%), stones (5 -28%), progressive hydroureteronephrosis (3 -17%) or stones (2 -11%). Conservative initial management (catheterizations, prophylaxis antibiotics) was effective in half. The remaining nine were defined as Complicated LUTD and underwent CV. After a mean follow-up of 11.3 months, follow up showed improved hydronephrosis in all nine patients (100%). Recurrent UTI were no longer seen in 8 of 9, although 3 required bladder irrigations; bladder stones did not recur after CV; the kidney stones needed further intervention. Revision of the CV was required in 2 cases (11%) at 12 and 24 months postoperatively due to stoma stenosis. CV is a relatively simple and effective procedure representing a pragmatic solution for managing Complicated LUTD in complex long-term institutionalized pediatric palliative care patients with neuropathic bladders.CV is a relatively simple and effective procedure representing a pragmatic solution for managing Complicated LUTD in complex long-term institutionalized pediatric palliative care patients with neuropathic bladders.